Penetrating Brain Injury by Multiple Low-Velocity Objects: Report of Two Rare Cases and Review of Literature - Baishya, Basanta Kumar; Dutta, Deep; Singh, R. K.; Singh, B. K.; Hussain, Zakir; Bhuyan, M. (Indian Journal of Neurotrauma, 2015)
We are reporting two rare cases of multiple penetrating brain injuries by an indigenously made traditional fishing gear used in an Indian village. Although penetrating injury from varied objects (viz., arrow, smear gun, knife, rod, bullets, etc.) have been reported earlier in the literature, but low-velocity penetrating brain injury by multiple objects is the first to our knowledge. In this report, we discuss the surgical management and outcome with relevant review of literature.
Keywords: fishing gear; multiple penetrating brain injury; low velocity